Islamic history : a framework for inquiry - Humphreys, R. Stephen (Princeton University Press, 1991)
Combining a bibliographic study with an inquiry into method, it opens with a survey of the principal reference tools available to historians of Islam and a systematic review of the sources they will confront. Problems of method are then examined in a series of chapters, each exploring a broad topic in the social and political history of the Middle East and North Africa between A.D. 600 and 1500. The topics selected represent a cross-section of Islamic historical studies, and range from the struggles for power within the early Islamic community to the life of the peasantry. Each chapter pursues four questions. What concrete research problems are likely to be most challenging and productive? What resources do we possess for dealing with these problems? What strategies can we devise to exploit our resources most effectively? What is the current state of the scholarly literature for the topic under study? -- Publishers description.